PERSONALITY OF ALICIA ON A BEAUTIFUL MIND MOVIE DIRECTED BY RON HOWARD: A PSYCHOANALYTIC APPROACH. - Badres, Ibrahim Afif (2010)
The major problem of this study is how the personality of major character's in personality of Alicia on A Beautiful Mind, resulted from unhandled problem she encounters. The aim of this study is to reveal the personality structure of the major character, which influences her behavior, using the mean of structural and psychoanalytic analysis. The object of this study is the personality of Alicia and it is focused on one of the major characters, namely Alicia. The benefit of the study is to give some contributions in the application of psychoanalytic approach in literary study and to fulfill the requirement for getting bachelor degree in English department. This study uses library data. The primary data are taken from the movie itself, while the secondary data from some criticism and information needed. The method of data collection is description and the study employs Sigmund Freud's psychoanalysis to answer the problem. The out come of the study shows that the problem that the major character encounters causes the conflicts of her mental condition. Alicia as a women character can be seem her personality according to Freud's Theory. In this case she accompanies to psychiatric to solve his problem. For that reason she needs to visit many places that have relation with John Nash's memories.Besides, she also meets his friends who have an information about his problem as Sol and Brender.